Protective role of parenthood on age-related brain function in mid- to late-life - Edwina R. Orchard; Sidhant Chopra; Leon Q. R. Ooi; Pansheng Chen; Lijun An; Sharna D. Jamadar; B. T. Thomas Yeo; Helena J. V. Rutherford; Avram J. Holmes (Proceedings of the National Academy of Sciences, 2025)
The experience of human parenthood is near ubiquitous and can profoundly alter one’s body, mind, and environment. However, we know very little about the long-term neural effects of parenthood for parents themselves, or the implications of pregnancy and caregiving experience on the aging adult brain. Here, we investigate the link between the number of children parented and age on brain function in 19,964 females and 17,607 males from the UK Biobank. In both females and males, parenthood was positively correlated with functional connectivity, such that higher number of children parented was associated with higher connectivity, particularly within the somato/motor network. Critically, the spatial topography of parenthood-linked effects was inversely correlated with the impact of age on functional connectivity across the brain for both females and males, such that the connections that were positively correlated with number of children were negatively correlated with age. This result suggests that a higher number of children is associated with patterns of brain function in the opposite direction to age-related alterations. Overall, these results indicate that the changes accompanying parenthood may confer benefits to brain health across the lifespan, altering aging trajectories, consistent with animal models of parenthood and preliminary findings of “younger-looking” brain structure in human parents. Observing this effect in both females and males implicates the caregiving environment, rather than pregnancy alone, and highlights the importance of future work to disentangle the underlying mechanisms related to the direct impact of caregiving, the indirect impact of the environment, and the result of covarying sociodemographic factors.